Increasing Assertive Behavior in Adolescents in Islamic Boarding Schools Through Assertive Training - Nuris Yuhbaba, Zidni; Arif Budiman, M.Elyas; Sholihah Erdah Suswati, Wahyi; Wirasakti, Guruh (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction: Assertive behavior is the ability to communicate the individual's want, feel, and think to others honestly and openly while respecting personal and other people's rights. One way to increase assertiveness in adolescents is through assertive training activities where this activity presents systematic activities that can develop and train individuals' abilities to express their thoughts, feelings, desires, and needs confidently. The purpose of this study was to analyze the change in assertive behavior of adolescents living in Islamic boarding schools through assertive training.Method: This was pre-experimental research with pre-post design.  The sample was 80 respondents which were obtained by the purposive sampling technique. The measuring instrument uses assertive behavior questionnaires and data analysis using the Wilcoxon Paired testResults: The results of the analysis of assertive behavior in adolescents before the intervention were in a low category (42.5%) and after the intervention, adolescent assertive behavior was in a good category (46.3%). The results showed a p-value of 000 which is result indicated that there was an increase in the assertive behavior of adolescents living in Islamic boarding schools through assertive training.Conclusions: Adolescents with high assertiveness are able to control their emotions, mental health and have good coping with solving personal and social problems, and are able to express their wishes firmly to others